Coagulability in Obstructive Sleep Apnea. Issue 6 (2011) - Liak, Christina; Fitzpatrick, Michael
Abstract : BACKGROUND: Obstructive sleep apnea (OSA) is a common disorder that affects both quality of life and cardiovascular health. The causal link between OSA and cardiovascular morbidity/mortality remains elusive. One possible explanation is that repeated episodes of nocturnal hypoxia lead to a hypercoagulable state that predisposes patients to thrombotic events. There is evidence supporting a wide array of hematological changes that affect hemostasis (eg, increased hematocrit, blood viscosity, platelet activation, clotting factors and decreased fibrinolytic activity). OBJECTIVE: To provide a comprehensive review of the current evidence associating OSA with increased coagulability, and to highlight areas for future research. METHODS: Keyword searches in Ovid Medline were used to identify relevant articles; all references in the articles were searched for relevant titles. The Web of Science was used to identify articles citing the relevant articles found using the Ovid Medline search. All original peer-reviewed articles, meta-analyses and systematic reviews regarding the pertinent topics between 1990 and present were selected for review. RESULTS: Hematocrit, blood viscosity, certain clotting factors, tissue factor, platelet activity and whole blood coagulability are increased in patients with OSA, while fibrinolysis is impaired. CONCLUSION: There is considerable evidence that OSA is associated with a procoagulant state. Several factors are involved in the procoagulant state associated with OSA. There is a need for adequately powered clinical studies involving well-matched control groups to address potential confounding variables, and to accurately delineate the individual factors involved in the procoagulant state associated with OSA and their response to treatment.